Spindle cell rhabdomyosarcomas: With TFCP2 rearrangements, and novel EWSR1::ZBTB41 and PLOD2::RBM6 gene fusions. A study of five cases and review of the literature - Bradová, Martina; Mosaieby, Elaheh; Michal, Michael; Vaněček, Tomáš; Ing, Stanislav Kormunda; Grossmann, Petr; Koshyk, Olena; Kinkor, Zdeněk; Laciok, Šimon; Nemcová, Antónia; Straka, Ľubomír; Farkas, Mihaela; et al. (Histopathology, 2024)
AIMS: Spindle-cell/sclerosing rhabdomyosarcomas (SS-RMS) are clinically and genetically heterogeneous. They include three well-defined molecular subtypes, of which those with EWSR1/FUS::TFCP2 rearrangements were described only recently. This study aimed to evaluate five new cases of SS-RMS and to perform a clinicopathological and statistical analysis of all TFCP2-rearranged SS-RMS described in the English literature to more comprehensively characterize this rare tumour type. METHODS AND RESULTS: Cases were retrospectively selected and studied by immunohistochemistry, fluorescence in situ hybridization with EWSR1/FUS and TFCP2 break-apart probes, next-generation sequencing (Archer FusionPlex Sarcoma kit and TruSight RNA Pan-Cancer Panel). The PubMed database was searched for relevant peer-reviewed English reports. Five cases of SS-RMS were found. Three cases were TFCP2 rearranged SS-RMS, having FUSex6::TFCP2ex2 gene fusion in two cases and triple gene fusion EWSR1ex5::TFCP2ex2, VAX2ex2::ALKex2 and VAX2intron2::ALKex2 in one case. Two cases showed rhabdomyoblastic differentiation and spindle-round cell/sclerosing morphology, but were characterized by novel genetic fusions including EWSR1ex8::ZBTB41ex7 and PLOD2ex8::RBM6ex7, respectively. In the statistical analysis of all published cases, CDKN2A or ALK alterations, the use of standard chemotherapy and age at presentation in the range of 18-24 years were negatively correlated to overall survival. CONCLUSION: EWSR1/FUS::TFCP2-rearranged SS-RMS is a rare rhabdomyosarcoma subtype, affecting predominantly young adults with average age at presentation 34 years (median 29.5 years; age range 7-86 years), with a predilection for craniofacial bones, rapid clinical course with frequent bone and lung metastases, and poor prognosis (3-year overall survival rate 28%).
Keywords: Gene Fusion; protein EWS vázající RNA; proteiny vázající RNA; Rhabdomyosarcoma; rhabdomyosarkom; Humans; DNA-Binding Proteins; lidé středního věku; DNA vazebné proteiny; dítě; Transcription Factors; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; Child; Procollagen-Lysine, 2-Oxoglutarate 5-Dioxygenase; RNA-Binding Protein EWS; Aged; mladý dospělý; dospělí; senioři; lidé; nádorové biomarkery; lysinhydroxylasa; Adult; hybridizace in situ fluorescenční; Middle Aged; Retrospective Studies; Adolescent; Aged, 80 and over; Young Adult; senioři nad 80 let; retrospektivní studie; transkripční faktory; fúze genů; RNA-Binding Proteins; mladiství